Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2016)
A dataset containing 11 species occurrences available in GBIF matching the query: { "and" : [ "TaxonKey is Picumnus aurifrons Pelzeln, 1870", "Country is Colombia" ] } The dataset includes 11 records from 4 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0002853-160509122628363/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences